2021
DOI: 10.1111/mec.15933
|View full text |Cite
|
Sign up to set email alerts
|

Distinct methylome patterns contribute to ecotypic differentiation in the growth of the storage organ of a flowering plant (sacred lotus)

Abstract: DNA methylation is an epigenetic modification involved in phenotypic diversity, plant development, and environmental responses. However, the mechanisms of DNA methylation underpinning the adaption of lotus (Nelumbo nucifera) ecotypes to high and low latitudes remain unsolved, especially adaptive evolution of their storage organs. Tropical and temperate lotus ecotypes have thin and enlarged rhizomes which are adapted to low and high latitudes, respectively. Here, we investigated the DNA methylomes and transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…Recent studies have found that some hyperaccumulators with limited genetic variation among populations still have a wide range of phenotypes in different metalliferous habitats ( Chen et al, 2015 ). Epigenetic variation which can regulate phenotypic variation could be one potentially important way for plant in response to environmental changes ( Niederhuth and Schmitz, 2014 ; Wibowo et al, 2016 ; Li et al, 2021 ). DNA methylation is one of the main epigenetic mechanisms enabling adaptation of plants in complex environments ( Niederhuth and Schmitz, 2014 ; Chang et al, 2019 ; Perrone and Martinelli, 2020 ; Li et al, 2021 ; Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that some hyperaccumulators with limited genetic variation among populations still have a wide range of phenotypes in different metalliferous habitats ( Chen et al, 2015 ). Epigenetic variation which can regulate phenotypic variation could be one potentially important way for plant in response to environmental changes ( Niederhuth and Schmitz, 2014 ; Wibowo et al, 2016 ; Li et al, 2021 ). DNA methylation is one of the main epigenetic mechanisms enabling adaptation of plants in complex environments ( Niederhuth and Schmitz, 2014 ; Chang et al, 2019 ; Perrone and Martinelli, 2020 ; Li et al, 2021 ; Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic variation which can regulate phenotypic variation could be one potentially important way for plant in response to environmental changes ( Niederhuth and Schmitz, 2014 ; Wibowo et al, 2016 ; Li et al, 2021 ). DNA methylation is one of the main epigenetic mechanisms enabling adaptation of plants in complex environments ( Niederhuth and Schmitz, 2014 ; Chang et al, 2019 ; Perrone and Martinelli, 2020 ; Li et al, 2021 ; Chen et al, 2022 ). Changes of DNA methylation in response to environmental stresses can be relatively stable, and establish a DNA methylation-dependent stress memory to the offspring ( Wibowo et al, 2016 ; Williams and Gehring, 2017 ; Sudan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] studied the genetic diversity of the wild Asian lotus from Northern China and provided essential resources for the Chinese wild lotus. Recently, research on DNA methylation in the lotus genome has been greatly promoted and conducted successfully [ 13 , 14 ]. However, studies on the mutation rate and demographic history of lotus are relatively few and evolutionary questions related to extinction, competition, and adaptation in lotus remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the functions of phenotypic plasticity in rapid environmental response have been well-accepted, its downstream regulatory roles are still under hot debates (Foret et al, 2012;Neri et al, 2017;Li et al, 2018Li et al, , 2021Smith et al, 2020). In a "standard" model, the methylation of CpG islands within promoter region is generally correlated with the transcriptional repression (Halpern et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During the endodermal development, hypermethylation of one CpG island within Forkhead box A2 (FOXA2) promoter might contribute to the active transcription of this gene (Halpern et al, 2014). In contrast to the widely studied functions of promoter methylation, the role of gene body methylation is still uncertain and perplexing, as it has been reported to be involved in negative/positive regulations at the transcript levels, alternative splicing, mitigation of transcriptional noise, and maintenance of transcriptional homeostasis (Foret et al, 2012;Neri et al, 2017;Li et al, 2018Li et al, , 2021. Collectively, these results suggest that the regulatory roles of DNA methylation in transcription might be far more complicated than what we have known.…”
Section: Introductionmentioning
confidence: 99%